2017
DOI: 10.1002/cphc.201700503
|View full text |Cite
|
Sign up to set email alerts
|

How Osmolytes Counteract Pressure Denaturation on a Molecular Scale

Abstract: Life in the deep sea exposes enzymes to high hydrostatic pressure which decreases their stability. For survival, deep sea organisms tend to accumulate various osmolytes, most notably trimethylamine N-oxide (TMAO) used by fish, to counteract pressure denaturation. Yet, exactly how they work still remains unclear. Here, we use a rigorous statistical thermodynamics approach to clarify the mechanism of osmoprotection. We show that the weak, non-specific, and dynamic interactions of water and osmolytes with protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 74 publications
(239 reference statements)
0
22
0
Order By: Relevance
“…[101] The unfavorability of protein-osmolyte interactions leads to preferentiale xclusion of osmolytes from protein surfaces and more favorable free energies for compact configurations. [102] Ap lausible physicalr ationalization of the combinedp ressure and osmolyte dependence of gD-crystallin LLPS, which needs to account also for the role of void volumes [98] in pressures ensitivity,w ill be discussed in Section4 below.…”
Section: Pressure-and Osmolyte-dependent Llps Of Aglobular Protein: Ementioning
confidence: 99%
See 3 more Smart Citations
“…[101] The unfavorability of protein-osmolyte interactions leads to preferentiale xclusion of osmolytes from protein surfaces and more favorable free energies for compact configurations. [102] Ap lausible physicalr ationalization of the combinedp ressure and osmolyte dependence of gD-crystallin LLPS, which needs to account also for the role of void volumes [98] in pressures ensitivity,w ill be discussed in Section4 below.…”
Section: Pressure-and Osmolyte-dependent Llps Of Aglobular Protein: Ementioning
confidence: 99%
“…[183][184][185][186][187] Nonetheless, it is generally agreedt hat TMAO confers stability to more compact protein configurations because it interacts unfavorably with proteins, av iew that is supported by the observation that TMAO is depleted around protein surfaces, but forms strongh ydrogen bonds to water. [102,183,188] The degree of unfavorable interaction between TMAO and different amino acid residues differs as it depends on the residue involved. Nonetheless, experimental evidencep oints to ag eneralo verall exclusion of TMAO from both hydrophobic and polar surfaces of proteins.…”
Section: At Entative Rationalization Of T- P- and Tmao-dependentpromentioning
confidence: 99%
See 2 more Smart Citations
“…14 Using neutron scattering experiments TMAO was earlier shown to interact directly with urea and offset its action on protein by Meersman et al 15 On the contrary, both experimental 16 as well as computational 17 studies have suggested that the enhancement of waterstructuring by TMAO is responsible for the preservation of the protein in its native state, not only from chemical denaturation but also from pressure induced structural collapse. 18 A very recent study by Dias and co-workers shows a competing mechanism of TMAO on Trp cage mini proteins, which stabilizes charge-charge interactions, induces collapse of the backbone and causes swelling of peptide with greater degree of hydrophobic residue. 19 Among other osmolytes, trehalose mediated counteraction of the effect of urea on a small peptide has been investigated thoroughly by Paul and Paul using extensive MD simulations.…”
Section: Introductionmentioning
confidence: 99%